Otyłość a zaburzenia snu, zaburzenia wzorca żywienia oraz kontrola czynników związanych ze zdrowiem = Obesity and sleep disorders, feeding pattern disorders and control of factors related to health - Sykut, Anna; Ślusarska, Barbara (Journal of Education, Health and Sport, 2016)
Sykut Anna, Ślusarska Barbara. Otyłość a zaburzenia snu, zaburzenia wzorca żywienia oraz kontrola czynników związanych ze zdrowiem = Obesity and sleep disorders, feeding pattern disorders and control of factors related to health. Journal of Education, Health and Sport. 2016;6(5):266-275. eISSN 2391-8306. DOI http://dx.doi.org/10.6084/m9.figshare.3382984 http://ojs.ukw.edu.pl/index.php/johs/article/view/3524 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.04.2016. Revised 25.04.2016. Accepted: 17.05.2016. Otyłość a zaburzenia snu, zaburzenia wzorca żywienia oraz kontrola czynników związanych ze zdrowiem Obesity and sleep disorders, feeding pattern disorders and control of factors related to health Anna Sykut1, Barbara Ślusarska2 1Klinika Chirurgii Plastycznej Linea Corporis w Warszawie 2Zakład Medycyny Rodzinnej i Pielęgniarstwa Środowiskowego, Wydział Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie 1Linea Corporis Plastic Surgery Clinic in Warsaw 2Department of Family Medicine and Community Nursing), Faculty of Health Sciences, Medical University of Lublin Słowa kluczowe: otyłość, zburzenia snu, zmiany wzorca żywienia, dorośli. Key words: obesity, sleep disorders, alterations in feeding pattern, adults. Streszczenie Wprowadzenie: Współcześnie występowanie otyłości określa się mianem globalnej epidemii. Prozdrowotna modyfikacja stylu życia jest istotnym wyzwaniem, mającym wpływ na wykluczenie niektórych chorób cywilizacyjnych. Cel pracy: Celem pracy był przegląd piśmiennictwa i jego analiza pod kątem wybranych czynników związanych z otyłością u osób dorosłych. Przedstawiono związek między otyłością a zaburzeniami snu, zaburzeniami odżywiania oraz kontrolą czynników związanych ze zdrowiem. Zastosowano metodę analizy piśmiennictwa. Przeglądu literatury dokonano na podstawie danych zawartych w bazie Google Scholar oraz informacji dostępnych na stronach internetowych. Skrócony opis stanu wiedzy: Osoby z wyższym BMI śpią dłużej, a jednocześnie im większa masa ciała, tym jakość snu oceniana jest jako niższa. Udowodniono, że coraz więcej osób podjada w porze nocnej oraz że apetyt zwiększa się w sytuacjach stresowych. Kluczową rolą w zmniejszeniu ryzyka powstania otyłości jest kontrola stanu zdrowia oraz odpowiednie odżywianie. Podsumowanie: Coraz liczniejsze dowody potwierdzają zależność między otyłością, a zaburzeniami snu, zmienionym wzorcem żywienia oraz zmniejszoną kontrolą stanu zdrowia. Abstract Introduction: Today, obesity is defined as a global epidemic. A pro-health lifestyle modification is a major challenge affecting the exclusion of certain diseases of civilization. Aim of the study: The aim of this study was to review and analyze the literature with respect to the selected factors associated with obesity in adults. The relationship between obesity and sleep disorders, feeding disorders as well as control of factors related to health were presented. The method of literature analysis was applied. The literature review was based on data contained in the Google Scholar database and information available on websites. Brief description of knowledge: People with the higher BMI sleep longer, while the greater the weight, the quality of sleep is judged to be lower. It has been proven that more and more people snack late at night and that the appetite increases in stressful situations. A key role in reducing the risk of obesity is health control and adequate nutrition. Summary: Mounting evidence validates the relationship between obesity and sleep disorders, an altered feeding pattern as well as reduced health control.